Equilibrium and kinetic study for the reaction of Trans-K[Cr(ox}z(H20)2).3Hz0 with 4-aminoantipyrine - Aziz, B. K.; Jubrael, K. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A   new   complex  of   Cr(UI)   has   been   prepared.  The   kinetics  and eqailibrium study of  the substitution reaction   for  the complex TransÂ KfCr(ox)z(H 0)2].3l--h0 {T I }, with 4-aminoantipyrine {AAP}, bave been perÂ£Qrm d      in  aqueous  media   at  .(pH. = 4.9,   5.6 and 6.0)   (!!?0.4M NaN03).   Activation  pararrieters   for  the  reac(ions are  {Eat= l.89l  kCalmor 1 ,        l:t=89.29  kCal  mo1"1     and     t\S  1     = 0.281   Cal.  mor1)    and1 (Ea2=0.487kCal mort, .1\Ht!=6..2.Cl3 kCal mort  and   t1S 2 = -92.8 Cal mor). The  observed rate constants are  in  good  agreement with  substitutionrea